Dietary Iodine Can Effectively Alleviate the Adverse Effects of Fermented Rapeseed Meal on the Growth, Liver Health, and Antioxidant Capacity of Tilapia (GIFT, Oreochromis niloticus) - Di Peng; Ya-Xue Li; Li-Xue Dong; Ke Cheng; Hua Wen; Juan Tian; Jian-Min Zhang; Yang-Yang Liu; Wei-Hua Gao; Yong Min; Ming-Dian Liu; Ming Jiang (Fishes)
An 8-week feeding trial was conducted to evaluate the effects of dietary fermented rapeseed meal (FRM), potassium iodide, and their interactions on growth performance, approximate composition, and antioxidant capacity in tilapia, Oreochromis niloticus (initial body weight: 3.50 ± 0.15 g). Six isonitrogenous and isolipidic diets from a 2 × 3 factorial design were formulated with two levels of FRM (25.8 and 51.6%) and three levels of potassium iodide (0, 6, and 12 mg/kg), respectively. The results indicated that dietary levels of FRM and iodine had no significant influence on the SR of tilapia but exerted significant effects on weight gain (WG), specific growth rate (SGR), feed intake (FI), hepatosomatic index, and viscerosomatic index. The WG, SGR, and FI of tilapia in the 51.6% FRM groups were significantly lower than those in other groups (p < 0.05), and iodine inclusion in the 51.6% FRM diet significantly enhanced WG, SGR, and FI of tilapia (p < 0.05). Dietary iodine significantly increased the whole-body and muscle lipid content in the tilapia (p < 0.05). The content of total bilirubin (T-Bil) and the activities of aspartate aminotransferase (AST) and alanine aminotransferase (ALT) in the tilapia serum were significantly reduced by the inclusion of 6–12 mg/kg iodine in 51.6% FRM level (p < 0.05), and the serum total triiodothyronine content was significantly elevated by the supplementation of 12 mg/kg iodine (p < 0.05). Significant interactions between dietary FRM and iodine were found in serum T-Bil content and triglyceride and AST activity (p < 0.05). Dietary supplementation of iodine in high FRM diets (51.6%) significantly increased the activities of total superoxide dismutase (T-SOD), catalase (CAT), and total antioxidant capacity (T-AOC) and decreased the content of malondialdehyde (MDA) in the liver of tilapia (p < 0.05). The activity of T-SOD, CAT, and T-AOC and the content of MDA in the liver of tilapia significantly interacted with the levels of dietary FRM and iodine (p < 0.05). Furthermore, the liver cell structure was further ameliorated, and the liver health status was significantly enhanced in each iodine treatment group.